La contribution féministe à l'étude de la déviance en criminologie - Parent, Colette (Criminologie, 1992)
Beginning in the 70s, the silence on the question of women in criminology was broken by a feminist series of works that was set upon the questioning and updating of knowledge in the social sciences and in criminology. This article concerns the conception of deviance in feminist studies dealing with the "criminality" and criminalization of women. The author finds that the feminists adopt a firmly empathetical approach toward women offenders, which enables them to depart from the traditional concepts of deviance and the develop analyses that go beyond the known context of questioning in the discipline. The feminist approach also makes it possible to review the positions to be taken regarding the crime policies that should be applied.